Peningkatan Kemampuan Inovasi UKM Batik berbasis Stimulasi Intelektual, Supervisi Organisasional, Dan Akumulasi Manajemen Pengetahuan: Increasing the Innovation Capabilities of Batik SMEs, Organizational Supervision, and Knowledge Management Accumulation - Suharto, Sulistyo; Marno Nugroho; Yuniar Dwi Lestari (Universitas Muhammadiyah Surakarta, 2022)
The research of this thesis is intended to identify and analyze how the influence given by Stimulation of Leadership, Organizational Supervision, and Accumulation of Knowledge Management. The population in this study were all batik employees in the city of Semarang. The number of samples taken from a population of 100 respondents was determined using the purposive sampling method and the Lameshow formula. The data analysis method used is quantitative analysis using multiple linear regression analysis to determine the value and nature of the influence of the variables studied.